Functional equations in the secondary school - Mačys, Juozas Juvencijus (Lietuvos matematikos rinkinys, 2011)
Secondary school in Lithuania goes over to modules in the mathematics syllabi. Teachers need various proof methods for solving problems of more complicated (olympiad) modules. The paperdiscusses the module of functional equations. The books and papers dealing with this question are pointed out. Some typical solving errors are discussed.
Keywords: mathematics syllabi; functional equations; olympiads